1979
DOI: 10.2134/jeq1979.00472425000800030027x
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Production of Wheat Grain Irrigated with Municipal Waste Water and Pump Water

Abstract: Experiments were conducted in southern Arizona to study the effects of irrigating wheat (Triticum aestivum L.) with a mixture of pump water and waste water and with pump water alone on wheat growth, grain yield, grain quality, soil properties, and irrigation water quality.In small plot research, wheat irrigated with the pump water‐waste water mixture produced taller plants, more heads per unit area, heavier seeds, higher grain yields, and higher straw yields than did wheat grown with only pump water. When larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
2
7
0
2
Order By: Relevance
“…The considerably higher total nitrogen content in the sewage effluent (28.1 mg L -1 ) than in the groundwater (1.4 mg L -1 ) could explain the higher nitrogen uptake of crops irrigated by the sewage effluent (Table 5). Our results for the effects of sewage application on crop nitrogen uptake are consistent with those of Day et al (1979), who found that N recovery in plants with wastewater was higher than the N recovery in plants material grown with groundwater.…”
Section: Nitrogen Uptakesupporting
confidence: 91%
“…The considerably higher total nitrogen content in the sewage effluent (28.1 mg L -1 ) than in the groundwater (1.4 mg L -1 ) could explain the higher nitrogen uptake of crops irrigated by the sewage effluent (Table 5). Our results for the effects of sewage application on crop nitrogen uptake are consistent with those of Day et al (1979), who found that N recovery in plants with wastewater was higher than the N recovery in plants material grown with groundwater.…”
Section: Nitrogen Uptakesupporting
confidence: 91%
“…Irrigation plays a vital role for its good growth and development (Razzaque et al, 1992). Some agronomic information regarding the feasibility and potential benefits of irrigation by wastewater on some crops and cultivable soils are available (Day et al, 1979;Bielorai et al, 1984;Chakrabarti andChakrabarti, 1988 &. However, these studies were done in climates and under irrigation by wastewater that were of different nature than that in Bangladesh.…”
mentioning
confidence: 99%
“…Baraman [7] observed adverse effects of sewage irrigation on growth and yield of pulses and oil seeds. In contrast, sewage irrigation improved the yield of several crops [8][9][10]. Sewage irrigation supported the population of N-fixers such as Azotobacter, Rhizobium and fungi involved in organic matter decomposition [11].…”
Section: Introductionmentioning
confidence: 99%